2013
DOI: 10.1111/psyp.12130
|View full text |Cite
|
Sign up to set email alerts
|

Why do we need to use a zero reference? Reference influences on the ERPs of audiovisual effects

Abstract: Using ERPs in the audiovisual stimulus, the current study is the first to investigate the influence of the reference on experimental effects (between two conditions). Three references, the average reference (AR), the mean mastoid (MM), and a new infinity zero reference (IR), were comparatively investigated via ERPs, statistical parametric scalp mappings (SPSM), and LORETA. Specifically, for the N1 (170-190 ms), the SPSM results showed an anterior distribution for MM, a posterior distribution for IR, and both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 44 publications
11
66
2
Order By: Relevance
“…We applied AR, LM, RESTs, and RESTr references to the ERP analysis within a simultaneous EEG-fMRI study and compared the reference effects on task-related ERP results which is a concern in cognitive neuroscience research and was confirmed to be affected by the reference choice (Kayser et al, 2007; Tian and Yao, 2013). ERP cortical source estimates were used as the golden standard in this comparison.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied AR, LM, RESTs, and RESTr references to the ERP analysis within a simultaneous EEG-fMRI study and compared the reference effects on task-related ERP results which is a concern in cognitive neuroscience research and was confirmed to be affected by the reference choice (Kayser et al, 2007; Tian and Yao, 2013). ERP cortical source estimates were used as the golden standard in this comparison.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the reference that best identifies neural activity and therefore be the basis of improved estimates of ERP features in the present EEG-fMRI recordings, we compared the reference effects of AR, LM, REST with the sphere head model (RESTs), and REST with the realistic head model (RESTr) on the task-related ERP effects and its distribution (e.g., discrimination-related posterior N1, VWM load-related parietal P300, and so on), which is the most concern in cognitive neuroscience research and was confirmed to be affected by the reference choice (Kayser et al, 2007; Tian and Yao, 2013). We hypothesized the change of reference methods would alter the task-related ERP effect itself (measured by statistical significance) and especially its scalp distribution (measured by SPSM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG and EOG signals were sampled at 1000 Hz, with a 0.1–100 Hz bandpass filter using a NuAmps digital amplifier system (Neuroscan Labs, El Paso, TX, USA). The tip of the nose was used as a reference during recording, and determination of the approximate zero reference using the reference electrode standardization technique (REST 2 ) was conducted off-line (Yao, 2001; Tian and Yao, 2013). Electrode impedances were kept below 5 kΩ.…”
Section: Methodsmentioning
confidence: 99%
“…REST transforms the EEG potentials referenced at any scalp points into the potentials referenced to a point located at infinity, far from all the possible neuronal sources and thus acting as an ideal neutral reference location. The merit of REST has been proved in event-related potentials (ERPs) (Tian and Yao, 2013), EEG spectrum (Yao et al, 2005), EEG coherence (Marzetti et al, 2007), and network analysis (Qin et al, 2010; Chella et al, 2016). …”
Section: Introductionmentioning
confidence: 99%